2007
DOI: 10.1177/154405910708601016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dentin Characteristics on Interfacial Nanoleakage

Abstract: Water emanating from dentinal tubules during air-drying and light-curing of adhesives leads to entrapment of droplets at the resin-dentin interface and contributes to nanoleakage. This study tested the null hypothesis that characteristics of substrate dentin and type of adhesive used for bonding would not affect the occurrence of nanoleakage. Three self-etch adhesives were used to bond to 4 types of dentin with different characteristics in 12 groups. After silver challenge, nanoleakage percentage was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
4
22
0
Order By: Relevance
“…These results would indicate that S 3 expresses less nanoleakage within the hybrid layer as well as water-tree nanoleakage. This result is in agreement with the previous study using a TEM 36) . HEMA can improve the bond strength to dentin, enhancing wetting of the dentin subsurface 37) , and preventing phase separation between the hydrophobic components and water 23) , resulting in the absence of water-tree nanoleakage formation.…”
Section: Discussionsupporting
confidence: 83%
“…These results would indicate that S 3 expresses less nanoleakage within the hybrid layer as well as water-tree nanoleakage. This result is in agreement with the previous study using a TEM 36) . HEMA can improve the bond strength to dentin, enhancing wetting of the dentin subsurface 37) , and preventing phase separation between the hydrophobic components and water 23) , resulting in the absence of water-tree nanoleakage formation.…”
Section: Discussionsupporting
confidence: 83%
“…The morphology of micro-bonding structures also significantly influences the bonding capability. 9,16,36,38 However, the information about the stress pattern and crack propagation at the bonded interface with the resin tags is unknown. In this study, the FE submodeling and element death techniques are proposed to investigate the 3D micro-mechanical behaviors at the bonded interface under shear bond testing.…”
Section: Discussionmentioning
confidence: 99%
“…Various resin tag penetration lengths and shapes caused by etching patterns and prism orientation influence the interfacial bonding performance. 9,16,36,38 However, the stress that transfers from the resin tags to the enamel substrate under a load is not clear. Presently, most fracture tests evaluate the structural performance without incorporating any means of relating the fracture path to the intrinsic structural properties.…”
Section: Introductionmentioning
confidence: 98%
“…30 Our previous study found that the hybridization quality of TB decreased more distinctly in comparison with SE when bonding to deep perpendicular dentine in vitro. 31 Strong air-blow after application of one-step adhesives was reported to be an effective method for removing excessive interfacial water and solvent. 32 However, this technique would cause more evaporative water flux to be shifted from dentinal tubules and entrapped into interfibrillar spaces of partially hydroxyapatite-depleted collagen fibrils.…”
Section: Discussionmentioning
confidence: 99%